2020
DOI: 10.1038/s41524-020-0275-z
|View full text |Cite
|
Sign up to set email alerts
|

High-harmonic generation from spin-polarised defects in solids

Abstract: The generation of high-order harmonics in gases enabled to probe the attosecond electron dynamics in atoms and molecules with unprecedented resolution. Extending these techniques to solids, which were originally developed for atomic and molecular gases, requires a fundamental understanding of the physics that has been partially addressed theoretically. Here, we employ timedependent density-functional theory to investigate how the electron dynamics resulting in high-harmonic emission in monolayer hexagonal boro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 79 publications
1
42
0
Order By: Relevance
“…5, the defect-state orbitals, located in the figure between the two vertical black lines, contribute significantly to the HHG yield compared to, e.g., the VB orbitals with indexes around 220. We note that the importance of the defect states for the HHG process was recently reported in a study on hexagonal boron nitride [37].…”
Section: B Effects Of Vacancies On the Hhg Spectrasupporting
confidence: 65%
See 2 more Smart Citations
“…5, the defect-state orbitals, located in the figure between the two vertical black lines, contribute significantly to the HHG yield compared to, e.g., the VB orbitals with indexes around 220. We note that the importance of the defect states for the HHG process was recently reported in a study on hexagonal boron nitride [37].…”
Section: B Effects Of Vacancies On the Hhg Spectrasupporting
confidence: 65%
“…For example, interband HHG is produced in a process resembling the atomic three-step model [11,12] and involves the following steps: (i) an electron tunnels from the valence band to the conduction band, producing a hole in the valence band; (ii) the electron and its corresponding hole propagate in the solid, driven by the external field; and (iii) they recombine and emit HHG radiation with a frequency that corresponds to the band-gap energy at the crystal momentum at which the recollision occurs [13]. More generally, it has emerged that several aspects of the HHG process in solids can be captured by solving the time-dependent Schrödinger equation for Bloch electrons in single-active-electron models [14][15][16][17][18][19][20][21] by applying many-electron approaches such as the semiconductor Bloch equations [22][23][24][25], by time-dependent densityfunctional theory (TDDFT) [26][27][28][29][30][31][32][33][34][35][36][37], and by time-dependent Hartree-Fock theory [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a concrete example, we study HHG in monolayer hexagonal boron nitride (h-BN) driven by infrared pulses linearly polarized in the crystal plane, and we compare the ERM results to solutions of the semiconductor Bloch equations (SBEs) [33,34]. In addition to the recent intense interest in HHG from two-dimensional materials [8,28,[35][36][37][38][39], h-BN is interesting due to its lack of an inversion center which leads to non-zero Berry connections and TDPs. Also, pulse propagation effects [40,41] can be neglected in monolayer materials.…”
mentioning
confidence: 99%
“…We found that the spatial width of the electron and hole wave packets can be almost one order of magnitude larger than the lattice constant, allowing for the imperfect recollisions. This suggests that the harmonic emission can probe the degree of spatial homogeneity of the periodic structure [25,39,[53][54][55] as well as the temporal dephasing introduced by e.g. electron correlation.…”
mentioning
confidence: 99%